2019
DOI: 10.1155/2019/2323761
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Chopped Basalt Fiber on the Performance of Porous Asphalt Mixture

Abstract: Porous asphalt mixture is a type of asphalt mixture with good drainage. However, it has poor tensile strength performance and durability. Chopped basalt fibers (CBF) have been proved to be an effective additive to improve the mechanical and fatigue performance of asphalt mixtures, but little attention has been paid on porous asphalt mixture. This paper examined the effect of chopped basalt fibers with different lengths (nonfiber, 3 mm, 6 mm, 9 mm, and 12 mm) and contents (3% and 4%) on the performance of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Pressure exerted from the aggregates will cause CF to bend and friction will increase between CF and other materials which lead to prevention of relative slippage of aggregates [10]. On the hand, study reported by Wang et al [12] this paper studies on chopped basalt fibers in asphalt mixture as the author concluded that 0.3 % of chopped basalt added in the mixture of porous asphalt mixture will resulted to an enhancement of the asphalt mixture integrity and crack propagation hindering. Furthermore, well combination between chopped basalt fiber and porous asphalt mixture contributed to 3-dimensional network structure as the state promptly reinforce the asphalt mixture which explained that fully coated chopped basalt fiber resulted great bonding connection journal.ump.edu.my/construction ◄ when it is mixing with porous asphalt [13].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 88%
“…Pressure exerted from the aggregates will cause CF to bend and friction will increase between CF and other materials which lead to prevention of relative slippage of aggregates [10]. On the hand, study reported by Wang et al [12] this paper studies on chopped basalt fibers in asphalt mixture as the author concluded that 0.3 % of chopped basalt added in the mixture of porous asphalt mixture will resulted to an enhancement of the asphalt mixture integrity and crack propagation hindering. Furthermore, well combination between chopped basalt fiber and porous asphalt mixture contributed to 3-dimensional network structure as the state promptly reinforce the asphalt mixture which explained that fully coated chopped basalt fiber resulted great bonding connection journal.ump.edu.my/construction ◄ when it is mixing with porous asphalt [13].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 88%
“…A three-point bending test can be utilized to analyze the lowtemperature behavior of the asphalt mixtures (Guo et al, 2020;Wang et al, 2019;Wang et al, 2018). Figure 6 shows that the freeze-thaw cycle, aging time, and basalt fiber content have stimulating effects on the flexural tensile intensity of asphalt.…”
Section: Three-point Bending Testmentioning
confidence: 99%
“…Xiong et al [15] investigated the influence of brucite fibers on asphalt mixtures, reporting improvement in the rut resistance, moisture susceptibility, and low-temperature cracking resistance of asphalt mixtures. Wang et al [16] evaluated the performance of porous asphalt mixtures modified with chopped basalt fibers and determined the optimal fiber length and content for improving the properties. In addition, previous research has indicated that asbestos fibers can improve the mechanical properties and thermal resistance of asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%